2017
DOI: 10.22159/ajpcr.2017.v10i2.15183
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction and Its Pharmacology: An Overview

Abstract: It has been estimated that currently over 150 million men worldwide suffer from erectile dysfunction (ED) and by 2025, the figure will increase beyond 322 millions. ED is the inability to achieve, and/or maintain penile erection sufficient for satisfactory sexual intercourse, and was previously regarded as the part of aging. It is associated with certain diseases and life style habits with a cause-effect relationship, including diabetes mellitus, hypertension, dyslipidemia, and cigarette smoking. International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Also, some researchers included iatrogenic endocrine disorders (amenorrhea, galactorrhoea and gynecomastia) as sexual dysfunction which is not termed under sexual dysfunction as per ICD-10, DSM-IV-TR, and therefore, may have affected the data on prevalence rates. Sexual dysfunction documented as antipsychotic-induced includes, decrease libido, erectile dysfunction, delay orgasm, anorgasmia, and ejaculation disorders (delayed or inhibited ejaculation, retrograde ejaculation, spontaneous ejaculation in the absence of sexual stimulation, decreased ejaculatory volume) [23][24][25]. In our study, the prevalence of sexual dysfunction with risperidone and haloperidol is 12.5 % each; decreased libido and premature ejaculation were found to be associated with them.…”
Section: Fig 3: Overall Action Was Taken For Suspected Drug Causing mentioning
confidence: 47%
“…Also, some researchers included iatrogenic endocrine disorders (amenorrhea, galactorrhoea and gynecomastia) as sexual dysfunction which is not termed under sexual dysfunction as per ICD-10, DSM-IV-TR, and therefore, may have affected the data on prevalence rates. Sexual dysfunction documented as antipsychotic-induced includes, decrease libido, erectile dysfunction, delay orgasm, anorgasmia, and ejaculation disorders (delayed or inhibited ejaculation, retrograde ejaculation, spontaneous ejaculation in the absence of sexual stimulation, decreased ejaculatory volume) [23][24][25]. In our study, the prevalence of sexual dysfunction with risperidone and haloperidol is 12.5 % each; decreased libido and premature ejaculation were found to be associated with them.…”
Section: Fig 3: Overall Action Was Taken For Suspected Drug Causing mentioning
confidence: 47%
“…Sildenafil is the first-line oral therapy that is effective for the treatment of ED. Though effective in circumventing the cause of ED, oral sildenafil therapy provides only short-term symptomatic relief of the condition [17]. The Asian MALES study has revealed that a majority or near majority of Asian men with self-reported ED have never sought treatment [18].…”
Section: Introductionmentioning
confidence: 99%